Legal Protection for Debtors Through Stay (Suspension of Execution) in the Postponement of Debt Payment Obligations (PKPU) to Ensure the Continuity of Business Operations - Sukamto Kusnadi; Gunawan Nachrawi (Fox Justi : Jurnal Ilmu Hukum, 2026)
Increasingly complex business activities are inseparable from the debt-receivables relationship which has the potential to cause problems when debtors experience financial difficulties. In these conditions, the Debt Payment Obligation Suspension (PKPU) mechanism is present as a legal means that aims to provide opportunities for debtors to restructure their debts and avoid bankruptcy. One of the important instruments in PKPU is stay (suspension of execution), which functions to suspend execution and collection actions by creditors. This study aims to analyze how the legal arrangement remains in PKPU as a form of legal protection for debtors and how effective its implementation is in ensuring the sustainability of business operations. The research method used is normative legal research with a statutory approach and a conceptual approach. The legal materials used consist of primary legal materials in the form of laws and regulations, especially Law Number 37 of 2004 concerning Bankruptcy and PKPU, as well as secondary legal materials in the form of relevant scientific literature and journals. The analysis was carried out qualitatively using descriptive-analytical techniques. The results of the study show that the legal stay arrangement in PKPU is constructed as an automatic suspension mechanism that limits creditors' execution actions and places debtors under supervision during the PKPU period, thereby providing preventive legal protection for debtors to carry out debt restructuring. In addition, the implementation of stays has proven to be effective in protecting debtors and maintaining business continuity because it is able to maintain productive assets and create room for negotiation, but this effectiveness is conditional because it is highly dependent on the debtor's good faith, the feasibility of the peace plan, and optimal supervision, so it has the potential to be abused if it is not balanced with adequate control.